Digital Transformation in Higher Education: An ArchiMate-Based Business Architecture Case Study - Xu-Liang Wang; Jing Li (IEEE Access)
In response to the multifaceted challenges faced by higher education institutions (HEIs), such as demographic shifts, labor market demands, and the need for digital learning, this study explores the digital transformation (DT) journey through a business architecture approach. Using a design science methodology, qualitative and inductive methods, and the ArchiMate language, the research offers theoretical insights and practical guidelines for HEIs undergoing similar transformations. Data were collected through semi-structured interviews with key stakeholders and through the learning platform of XYZ University. The study delineates comprehensive architecture views, including motivation, goals, outcomes, courses of action, value streams, capabilities, information, and business processes. It proposes a three-stage transformation pathway: digitization, digitalization, and digital transformation. At XYZ University, adopting digital technologies has enhanced student-teacher interactions, peer collaborations, and digital platform usage, improving academic performance and pass rates. Aligning the curriculum with industry needs has also increased employer and student satisfaction. The study concludes that successful DT in HEIs depends on developing a comprehensive business architecture. This integrated approach effectively guides HEIs toward realizing their DT objectives.